The effects of processing conditions on the morphology of single conjugated polymers. - Yeo, Hui Lin. (2010)
The photoluminescent lifetime of spun-cast single regioregular poly (3-hexylthiophene) (RR P3HT) was found to be significantly larger (2 – 3.5ns) than that of drop-cast chains and that in solution (<0.5ns), which likely implies a chain conformational dependence on the processing method used. Fluorescence intensity traces of drop-cast and spun-cast single chains were subsequently analyzed to elucidate the typical chain conformations adopted under these different processing conditions. Drop-cast single chains were proposed to either retain its extended conformation in CHCl3 solution, or adopt an ordered structure with hair-pin loops, giving rise to two corresponding distinct types of intensity traces. Spun-cast single chains were largely found to give neat intensity traces exhibiting discrete emission levels and clear off-states, suggesting a compact and collapsed disordered conformation favoring efficient energy funneling to one or a few low-energy exciton traps. These emissive centers of the collapsed chain were proposed to be intrachain aggregates consisting of closely π-stacked segments, therefore possessing weak oscillator strength and an extended radiative lifetime. This possibly explains the significantly increased photoluminescent lifetime observed in single spun-cast chains. Single-molecule photon antibunching experiments were also conducted in an attempt to verify the respective chain conformations by quantitatively determining the number of emitters in the corresponding single chains.